The Effect of Customer Relationship Management (CRM), Service Quality, and Value Creation on Customer Satisfaction among Customers of PT Pegadaian (Persero) Cisalak Branch, Depok - Andhi Dwy Noviono (Privietlab, 2021)
The research is aimed for identifying the impact of the Customer Relationship Management (CRM) (X1), the Service Quality (X2), and the Value Creation (X3) on Customer Satisfaction (Y) Customer in PT.Pegadaian (Persero) Cisalak Depok. The period of research is within Desember 2012 to February 2013. The method used is a method of analysis using the calculations Statistical Product and Service Solutions (SPSS) using regression and correlation. The population to be predicted in the research is customer of the PT.Pegadaian (Persero) Cisalak Depok, using 125 samples, which are carefully chosen to ensure so that the samples reflect the population. Measurement of the variables is done using the research instrument with a Likert scale. Used to test the validity of construct validity, test reliability while using a formula Cronbach Alpha. From the calculation results obtained that the number of variables X1 correlation of Y is 0,487 indicates a quite strong correlation of these two variables, the correlation rate of the Y variable X2 is 0,590 indicates a strong correlation of these two variables, the correlation of variables X3 digit of Y is 0,556 showing strong correlation between the two variables, correlation numbers X1, X2, and X3 of Y is 0,647 showing a strong relationship between the two variables. Based on the analysis of the obtained regression equation is Y = 2,665 + 0.106 X1 + 0,160 X2 + 0,268 X3. Where Y is Customer Satisfaction, X1 is the Customer Relationship Management, the Service Quality X2, and X3 are the Value Creation. Then from the calculated coefficients Standardized Coefficients column / Beta is obtained that the magnitude of the effect on Customer Relationship Management of Customer Satisfaction in PT.Pegadaian (Persero) Cisalak amounted to 23,7% for the remaining 76,3% is determined by other variables. The magnitude of the influence of Service Quality on Customer Satisfaction of customer in PT.Pegadaian (Persero) Cisalak was 34.8% for the rest of 65,2% determined by other variables. The magnitude of the influence of Value Creation on Customer Satisfaction of customer in PT.Pegadaian (Persero) Cisalak is 31% for the remaining 69% is determined by other variables. The magnitude of the influence of Customer Relationship Management, Service Quality and Value Creation reforms together on Customer Satisfaction of customer in PT.Pegadaian (Persero) Cisalak was 44,4% for the remaining 55,6% is determined by other variables.